PENGARUH PEMBERIAN TRAINING YANG BERBEDA TERHADAP MOTIVASI KERJA KARYAWAN INDUSTRI KECIL - Sunardi T Koesugito (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2018)
Small industry is as one of component in the structural of national economic has a great role in using of the potential of natural and human resource, that’s why the real sector of small industry must be developed both the quality and quantity.Some factors of hindrance of growing and developing of small industry need investigated accuracy so that the strategy of developing can be designed optimally. The objective of the research are, 1) to know the effect of kinds of training on the increasing of employee’s motivation, 2) to know the effect of age’s employee the less and more 40 years on increasing motivation, and 3) to know the effect of kinds of training on the increasing of manager team’s motivation. The population in the research are the employee and the manager in some of small industry in region ofSidoarjo and Gresik. Technique sampling use the simple random sampling, and the analysis of data use t-test because the all data is normal distribution. Conclusion of the research, those are, the first, there is increasing of employee’s work motivation after they joined training, but their increasing is not difference between laboratory training and outbond training, the second, employee’s work motivation age less 40 years increase bigger than age more 40 years , the third, there is not difference of manager team’s motivation result giving of job instruction training and coaching training,but training is given.